Den italienske variant – Fra Labriola til Gramsci - Sørensen, Gert (Slagmark - Tidsskrift for idéhistorie, 2018)
THE ITALIAN CASE - FROM LABRIOLA TO GRAMSCI Taking The Communist Manifesto (1848) as a point of departure, this article intends to emphasize the aporia in the works of Marx between Marx the scientist og Marx the politician, that furthermore reflects some of the main fractures between on one hand the theoretical interpretation of the capitalistic mode of production and on the other hand the strategic approaches characterizing the attempts of the European Socialist parties and the early European labour movement to overcome the ever returning crisis and the deep-rooted class conflicts. The specific Italian experiences offer the opportunity not only to discuss the philosophical and scientific contents of historical materialism but also to reactualize the political categories of democracy vis-à-vis the dictatorship of the proletariat and permanent revolution. In this respect, Antonio Labriola was a leading figure in the Italian debate of Marxism in the years between the 18th and the 19th Centuries, while Antonio Gramsci in the 1930ies revised the Marxist-Leninist tradition in the light of Fascism and the Stalinistic impasse of the Russian revolution.